1998
DOI: 10.1126/science.281.5382.1515
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Neuronal Growth Cone Responses from Repulsion to Attraction by Cyclic Nucleotides

Abstract: Nerve growth is regulated by attractive and repulsive factors in the nervous system. Microscopic gradients of Collapsin-1/Semaphorin III/D (Sema III) and myelin-associated glycoprotein trigger repulsive turning responses by growth cones of cultured Xenopus spinal neurons; the repulsion can be converted to attraction by pharmacological activation of the guanosine 3',5'-monophosphate (cGMP) and adenosine 3',5'-monophosphate signaling pathways, respectively. Sema III also causes the collapse of cultured rat senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
561
5
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 741 publications
(604 citation statements)
references
References 36 publications
36
561
5
2
Order By: Relevance
“…Growth cone collapse is probably the first event in inhibition, and many of the treatments that overcome inhibition of axonal growth also block growth cone collapse/repulsion 68,74 . Mechanistically, collapse and turning are the same, all that differs is the amount of growth cone that is exposed to inhibitors.…”
Section: Box 3 | Mechanisms Involved In Inhibition Of Axonal Growth Vmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth cone collapse is probably the first event in inhibition, and many of the treatments that overcome inhibition of axonal growth also block growth cone collapse/repulsion 68,74 . Mechanistically, collapse and turning are the same, all that differs is the amount of growth cone that is exposed to inhibitors.…”
Section: Box 3 | Mechanisms Involved In Inhibition Of Axonal Growth Vmentioning
confidence: 99%
“…For example, elevation of cyclic AMP (cAMP) overcomes inhibition by Mag and myelin 68,73 . Similarly, when either soluble Mag or myelin is presented to the growth cone in an asymmetric gradient, elevation of cAMP changes repulsion to attraction 74 …”
Section: Insight From Systems That Regenerate In Vivomentioning
confidence: 99%
“…In other studies, the bifunctional nature of Sema3A in the nervous system has been attributed to the differential availability of intracellular signaling effectors, such as cyclic nucleotides (cGMP) (Zhou et al, 2008). It was shown that elevating intracellular cGMP levels could switch a neuronal Sema3A response from repulsive to attractive (Song et al, 1998). In fact, differential expression of guanylate cyclase, which elevates cGMP levels, in different compartments of developing neurons determines the responses to Sema3A.…”
Section: Discussionmentioning
confidence: 99%
“…Between them, they regulate the formation of neuronal networks in many regions of the CNS, including the hippocampus, cerebral cortex, and olfactory system (Chedotal et al, 1998;Polleux et al, 1998;Schwarting et al, 2000;Pozas et al, 2001;Cloutier et al, 2002;Walz et al, 2002;Taniguchi et al, 2003). In addition to directing growth cone movements, they regulate the migration of cells, including neural crest and neuronal progenitor cells (Song et al, 1998;Eickholt et al, 1999;Bagnard et al, 2001;Kawasaki et al, 2002) and, thus, may play a role in shaping anatomic structures. Recent studies have demonstrated that Semas may also act as chemoattractants (Bagnard et al, 1998;de Castro et al, 1999;Polleux et al, 2000).…”
Section: Introductionmentioning
confidence: 99%